On interference, collegiality and co-authorship: Peer review of journal articles in management and organization studies - Brewis, Joanna (Organization (London, England), 2018)
Management and organization studies commentary on how authors experience peer review of journal papers suggests that it can be an overly interventionist process which reduces the originality and coherence of eventual publications. In the literature on co-authorship, this argument is reversed. Here, free riders who do not contribute fully to research collaborations and the practice of gift authorships are problematized, and it is argued that everyone involved in writing a published paper should be rewarded with co-authorship. In this article, qualitative interviews with 12 management and organization studies academics see respondents describing peer review as a transaction during which reviewers – and editors – actually co-author published papers. But their perspectives on this vary with the subject position from which they are speaking. When they speak as reviewers or editors, this co-authorship is depicted as a collegiate gift, a professional obligation or a process where authors might over-rely on reviewers’ generosity. When they speak as authors or their proxies, it is characterized as reproducing disciplinary orthodoxy and ethnocentric exclusion, perpetuating disciplinary cliques, creating disorganized papers and constituting excessive interference with authorial privilege. These various perspectives on peer review deserve more attention in our empirical studies of academic labour. They also suggest we should reflect more on when, how and why we collaborate in our research and on how much we should recognize additional co-authors on (or resist their input into) ‘our’ work.